A high-strength environment-resistant antistatic polarizer protective film and preparation method thereof
By using specific raw materials and processes, a high-strength environmentally resistant anti-static polarizer protective film was prepared, which solved the problem of insufficient strength and environmental resistance of the existing protective film, and achieved higher mechanical properties and environmental adaptability.
Patent Information
- Application Number
- CN202510272039.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The strength and environmental resistance of the existing polarizer protective films are insufficient, making it difficult to meet higher mechanical properties and environmental adaptability requirements.
A high-strength environmentally resistant antistatic polarizer protective film is prepared by mixing, stirring and baking treatment.
The mechanical properties and environmental resistance of the protective film are improved, ensuring its quality and quality in use, and are suitable for a wider market.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of display materials, and in particular to a high-strength environment-resistant antistatic polarizer protective film and a preparation method thereof. Background Art
[0002] The full name of polarizer is polarizing film. The imaging of LCD must rely on polarized light. All liquid crystals have two polarizing films in the front and back attached to the liquid crystal glass, forming a liquid crystal film with a total thickness of about 1mm.
[0003] In the patent document with application number "CN2016112 29683.3" and name "A Polarizer Protective Film", it is recorded that "the polarizer protective film is formed by coating an adhesive on one side of a polyester film to form an adhesive layer, and the adhesive consists of 35 to 60 parts by weight of an acrylate resin, 0.8 to 3.5 parts by weight of an antistatic agent, 0.2 to 2.5 parts by weight of a curing agent, 1.5 to 5 parts by weight of a leveling agent, and 29.5 to 62 parts by weight of a solvent; the resistance of the adhesive layer is below 1010Ω, and the polyester film adhesive layer is further bonded with a layer of release film. For the polarizer protective film provided by the present invention, when the release film is torn off and the adhesive layer of the protective film is bonded to the surface of the polarizer, after UV irradiation for 6 hours, the protective film and the polarizer are tightly bonded, and there is no bubble bulging or other phenomenon of the protective film and the polarizer falling off."
[0004] Although the polarizer protective film manufactured by the above patent document has advantages such as anti-static, its own strength and environmental resistance are relatively insufficient and still need further improvement. Based on this, the present invention provides a high-strength environmentally resistant anti-static polarizer protective film and a preparation method thereof to solve the above technical problems! Summary of the invention
[0005] The purpose of the present invention is to provide a high-strength environmentally resistant antistatic polarizer protective film and a preparation method thereof. The prepared high-strength environmentally resistant antistatic polarizer protective film not only has good mechanical properties, but also has excellent environmental resistance and antistatic properties, effectively ensuring its quality.
[0006] To achieve the above object, the present invention provides the following technical solutions: The first aspect of the present invention provides a high-strength, environment-resistant and antistatic polarizer protective film, which is composed of the following raw materials in parts by weight: 10 to 20 parts of polydimethylsiloxane, 3 to 6 parts of functional additives, 5 to 10 parts of polyvinylidene fluoride, 2 to 4 parts of synergistic additives, 3 to 6 parts of antioxidants and 20 to 50 parts of solvents.
[0007] Furthermore, the preparation process of the functional additive is as follows: The zirconia fiber is placed in an appropriate amount of γ-aminopropyltriethoxysilane at a solid-liquid ratio of 0.02 to 0.22 g / mL, treated at 120 to 220 r / min for 80 to 100 min, filtered, washed with deionized water for 2 to 4 times, and dried at 70 to 100° C. to constant weight to obtain modified zirconia fiber; The multi-walled carbon nanotubes are placed in an appropriate amount of deionized water and ultrasonically treated for 40 to 60 minutes at a solid-liquid ratio of 0.02 to 0.32 g / mL to obtain a suspension; An appropriate amount of modified zirconia fiber is placed in a suspension at a mass ratio of 0.1 to 0.4:1, and treated at 30 to 34°C and 80 to 110 r / min for 22 to 24 hours. After filtration, it is dried in an oven at 60°C for 24 hours. The obtained dry product is placed in a constant temperature device, and ozone is introduced into it. It is treated at 75°C for 30 to 34 minutes to obtain a functional additive.
[0008] Furthermore, the ozone introduction rate is 20-22 g / h, the concentration is 1000 ppm, and the introduction time is 30-34 min.
[0009] Furthermore, the preparation process of the synergistic aid is as follows: The potassium tetratitanate whiskers are placed in an appropriate amount of deionized water and ultrasonically dispersed for 20 to 30 minutes at a solid-liquid ratio of 0.05 to 0.15 g / mL to obtain a first solution; Place tin chloride pentahydrate in an appropriate amount of deionized water at a solid-liquid ratio of 0.12-0.22 g / mL, treat at 120-140 r / min for 20-30 min, add 0.13-0.23% oxalic acid solution by mass of tin chloride pentahydrate, continue stirring for 10-20 min, and obtain a second solution; The first solution is added to the second solution at a mass ratio of 0.03 to 0.23:1, and the pH is adjusted to 2.2 to 2.6 with sodium hydroxide, and the mixture is treated at 50 to 56° C. and 60 to 80 r / min for 200 to 240 min, and then dried at 70 to 80° C. to constant weight; The obtained dried product is placed in a vacuum calcination device and treated at 380-400° C. for 60-70 minutes to obtain an intermediate product; The basalt fiber is placed in an appropriate amount of γ-aminopropyltriethoxysilane at a solid-liquid ratio of 0.03-0.23 g / mL, treated at 80-100 r / min for 60-70 min, filtered, washed with deionized water for 2-4 times, and dried at 70-100° C. to constant weight to obtain modified basalt fiber; The modified basalt fiber is placed in an appropriate amount of N,N-dimethylformamide at a solid-liquid ratio of 0.11 to 0.28 g / mL and ultrasonically treated for 20 to 30 minutes. The intermediate product is then added thereto and treated in a 70°C water bath for 22 to 24 hours. After filtration, the fiber is washed with deionized water for 2 to 4 times and then dried at 70 to 80°C to constant weight to obtain a synergistic additive.
[0010] Furthermore, the oxalic acid solution is prepared by compounding oxalic acid and water in a mass ratio of 0.56 to 0.66:1.
[0011] Furthermore, the addition amount of the intermediate product is 11-22% of the modified basalt fiber.
[0012] Furthermore, the solvent is selected from any one of ethanol and acetone.
[0013] Furthermore, the antioxidant is selected from any one of antioxidant 1010, antioxidant 1076, and antioxidant CA.
[0014] The second aspect of the present invention: also provides a method for preparing the above-mentioned high-strength environment-resistant antistatic polarizer protective film, comprising the following steps: Step 1, accurately weighing polydimethylsiloxane, functional additives, parts of polyvinylidene fluoride, synergistic additives, antioxidants and solvents, and putting polydimethylsiloxane, functional additives, parts of polyvinylidene fluoride, synergistic additives, antioxidants and solvents into a mixing device for mixing and stirring to obtain a mixture; Step 2: coating the mixture on a molding device, and baking the molding device coated with the mixture to obtain a high-strength, environment-resistant, antistatic polarizer protective film.
[0015] Furthermore, the baking temperature is 220-240° C. and the baking time is 180-200 min.
[0016] Compared with the prior art, the present invention has the following beneficial effects: In the present invention, polydimethylsiloxane, functional additives, polyvinylidene fluoride, synergistic additives, antioxidants and solvents are used as raw materials. Polydimethylsiloxane, functional additives, polyvinylidene fluoride, synergistic additives, antioxidants and solvents are put into a mixing device for mixing and stirring to obtain a mixture, and then the mixture is coated on a molding device, and the molding device coated with the mixture is baked to obtain a high-strength environmentally resistant antistatic polarizer protective film. The high-strength environmentally resistant antistatic polarizer protective film prepared by the present invention not only has good mechanical properties, but also has excellent environmental resistance and antistatic properties, which effectively guarantees its quality. The high-strength environmentally resistant antistatic polarizer protective film and the preparation method thereof provided by the present invention have a broader market prospect and are more suitable for promotion. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] Example 1: This example provides a high-strength, environment-resistant, antistatic polarizer protective film, which is composed of the following raw materials in parts by weight: 10 parts of polydimethylsiloxane, 3 parts of functional additives, 5 parts of polyvinylidene fluoride, 2 parts of synergistic additives, 3 parts of antioxidants and 20 parts of solvents.
[0019] In this embodiment, it should be noted that polydimethylsiloxane was purchased from Jinan Yingyu Chemical Co., Ltd., and polyvinylidene fluoride was purchased from Suzhou Huida Plastics Import and Export Co., Ltd.
[0020] The preparation process of the functional additive is as follows: The zirconia fiber was placed in an appropriate amount of γ-aminopropyltriethoxysilane at a solid-liquid ratio of 0.02 g / mL, treated at 120 r / min for 80 min, filtered, washed twice with deionized water, and dried at 70°C to constant weight to obtain modified zirconia fiber; The multi-walled carbon nanotubes were placed in an appropriate amount of deionized water and ultrasonically treated for 40 min at a solid-liquid ratio of 0.02 g / mL to obtain a suspension; An appropriate amount of modified zirconia fiber was placed in a suspension at a mass ratio of 0.1 to 0.4:1, and treated at 30°C and 80 r / min for 22 hours. After filtration, it was dried in an oven at 60°C for 24 hours. The dried product was placed in a constant temperature device, and ozone was introduced into it. It was treated at 75°C for 30 minutes to obtain a functional additive.
[0021] Furthermore, the ozone introduction rate is 20 g / h, the concentration is 1000 ppm, and the introduction time is 30 min.
[0022] In this embodiment, it should be noted that the multi-walled carbon nanotubes were purchased from Shanghai Xiangtian Nanomaterials Co., Ltd., and the zirconium oxide fibers were purchased from Angxing New Carbon Materials Changzhou Co., Ltd.
[0023] The preparation process of the synergistic agent is as follows: The potassium tetratitanate whiskers were ultrasonically dispersed in an appropriate amount of deionized water at a solid-liquid ratio of 0.05 g / mL for 20 minutes to obtain a first solution; The tin chloride pentahydrate was placed in an appropriate amount of deionized water at a solid-liquid ratio of 0.12 g / mL, and treated at 120 r / min for 20 min. An oxalic acid solution with a mass percentage of 0.13% of the tin chloride pentahydrate was added thereto, and the stirring treatment was continued for 10 min to obtain a second solution; The first solution was added to the second solution at a mass ratio of 0.03:1, and the pH was adjusted to 2.2 with sodium hydroxide, and the mixture was treated at 50°C and 60 r / min for 200 min, and then dried at 70°C to constant weight; The obtained dried product was placed in a vacuum calcination device and treated at 380° C. for 60 min to obtain an intermediate product; Basalt fiber was placed in an appropriate amount of γ-aminopropyltriethoxysilane at a solid-liquid ratio of 0.03 g / mL, treated at 80 r / min for 60 min, filtered, washed twice with deionized water, and dried at 70°C to constant weight to obtain modified basalt fiber; The modified basalt fiber was placed in an appropriate amount of N,N-dimethylformamide at a solid-liquid ratio of 0.11 g / mL and ultrasonically treated for 20 minutes. The intermediate product was then added thereto and treated in a 70°C water bath for 22 hours. After filtration, it was washed twice with deionized water and then dried at 70°C to constant weight to obtain a synergistic additive.
[0024] Furthermore, the oxalic acid solution is prepared by mixing oxalic acid and water in a mass ratio of 0.56:1.
[0025] The addition amount of the intermediate product is 11% of the modified basalt fiber.
[0026] In this embodiment, it should be noted that the basalt fiber was purchased from Taian Zhirong Engineering Materials Co., Ltd.
[0027] Wherein, ethanol is selected as the solvent.
[0028] The antioxidant used is antioxidant 1010.
[0029] In addition, this embodiment also provides a method for preparing the above-mentioned high-strength environment-resistant antistatic polarizer protective film, comprising the following steps: Step 1, accurately weighing polydimethylsiloxane, functional additives, parts of polyvinylidene fluoride, synergistic additives, antioxidants and solvents, and putting polydimethylsiloxane, functional additives, parts of polyvinylidene fluoride, synergistic additives, antioxidants and solvents into a mixing device for mixing and stirring to obtain a mixture; Step 2: coating the mixture on a molding device, and baking the molding device coated with the mixture to obtain a high-strength, environment-resistant, antistatic polarizer protective film.
[0030] The baking temperature is 220°C and the baking time is 180 minutes.
[0031] Example 2: The preparation method of the high-strength environment-resistant antistatic polarizer protective film provided in this example is basically the same as that in Example 1, except that: the specific raw material composition and the specific preparation method of the high-strength environment-resistant antistatic polarizer protective film in this example are different; the specific raw material composition and the specific preparation method of the high-strength environment-resistant antistatic polarizer protective film in this example are as follows: A high-strength environment-resistant antistatic polarizer protective film is composed of the following raw materials in parts by weight: 15 parts of polydimethylsiloxane, 4 parts of functional additives, 7 parts of polyvinylidene fluoride, 3 parts of synergistic additives, 4 parts of antioxidants and 35 parts of solvents.
[0032] In this embodiment, it should be noted that polydimethylsiloxane was purchased from Jinan Yingyu Chemical Co., Ltd., and polyvinylidene fluoride was purchased from Suzhou Huida Plastics Import and Export Co., Ltd.
[0033] The preparation process of the functional additive is as follows: The zirconia fiber was placed in an appropriate amount of γ-aminopropyltriethoxysilane at a solid-liquid ratio of 0.12 g / mL, treated at 170 r / min for 90 min, filtered, washed with deionized water for 3 times, and dried at 85°C to constant weight to obtain modified zirconia fiber; The multi-walled carbon nanotubes were placed in an appropriate amount of deionized water and ultrasonically treated for 40 to 60 minutes at a solid-liquid ratio of 0.17 g / mL to obtain a suspension; An appropriate amount of modified zirconia fiber was placed in a suspension at a mass ratio of 0.3:1, treated at 32°C and 90r / min for 22 to 24 hours, filtered, and dried in an oven at 60°C for 24 hours. The obtained dry product was placed in a constant temperature device, and ozone was introduced into it, and treated at 75°C for 32 minutes to obtain a functional additive.
[0034] Furthermore, the ozone introduction rate was 21 g / h, the concentration was 1000 ppm, and the introduction time was 32 min.
[0035] In this embodiment, it should be noted that the multi-walled carbon nanotubes were purchased from Shanghai Xiangtian Nanomaterials Co., Ltd., and the zirconium oxide fibers were purchased from Angxing New Carbon Materials Changzhou Co., Ltd.
[0036] The preparation process of the synergistic agent is as follows: The potassium tetratitanate whiskers were ultrasonically dispersed in an appropriate amount of deionized water at a solid-liquid ratio of 0.1 g / mL for 25 minutes to obtain a first solution; The tin chloride pentahydrate was placed in an appropriate amount of deionized water at a solid-liquid ratio of 0.17 g / mL, and treated at 130 r / min for 25 min. An oxalic acid solution with a mass percentage of 0.18% of the tin chloride pentahydrate was added thereto, and the stirring treatment was continued for 15 min to obtain a second solution. The first solution was added to the second solution at a mass ratio of 0.13:1, and the pH was adjusted to 2.4 with sodium hydroxide, and the mixture was treated at 53°C and 70 r / min for 220 min, and then dried at 75°C to constant weight; The obtained dried product was placed in a vacuum calcination device and treated at 390° C. for 65 min to obtain an intermediate product; Basalt fiber was placed in an appropriate amount of γ-aminopropyltriethoxysilane at a solid-liquid ratio of 0.13 g / mL, treated at 90 r / min for 65 min, filtered, washed with deionized water for 3 times, and dried at 85°C to constant weight to obtain modified basalt fiber; The modified basalt fiber was placed in an appropriate amount of N,N-dimethylformamide at a solid-liquid ratio of 0.2 g / mL and ultrasonically treated for 25 minutes. The intermediate product was then added thereto and treated in a 70°C water bath for 23 hours. After filtration, the fiber was washed with deionized water for 2 to 4 times and then dried at 75°C to constant weight to obtain a synergistic additive.
[0037] Furthermore, the oxalic acid solution is prepared by mixing oxalic acid and water in a mass ratio of 0.61:1.
[0038] The addition amount of the intermediate product is 17% of the modified basalt fiber.
[0039] In this embodiment, it should be noted that the basalt fiber was purchased from Taian Zhirong Engineering Materials Co., Ltd.
[0040] Wherein, acetone is selected as the solvent.
[0041] Antioxidant 1076 was selected as the antioxidant.
[0042] In addition, this embodiment also provides a method for preparing the above-mentioned high-strength environment-resistant antistatic polarizer protective film, comprising the following steps: Step 1, accurately weighing polydimethylsiloxane, functional additives, parts of polyvinylidene fluoride, synergistic additives, antioxidants and solvents, and putting polydimethylsiloxane, functional additives, parts of polyvinylidene fluoride, synergistic additives, antioxidants and solvents into a mixing device for mixing and stirring to obtain a mixture; Step 2: coating the mixture on a molding device, and baking the molding device coated with the mixture to obtain a high-strength, environment-resistant, antistatic polarizer protective film.
[0043] The baking temperature is 230°C and the baking time is 190 minutes.
[0044] Example 3: The preparation method of the high-strength environmentally resistant antistatic polarizer protective film provided in this example is basically the same as that in Example 1, except that: the specific raw material composition and the specific preparation method of the high-strength environmentally resistant antistatic polarizer protective film in this example are different; the specific raw material composition and the specific preparation method of the high-strength environmentally resistant antistatic polarizer protective film in this example are as follows: A high-strength environment-resistant antistatic polarizer protective film is composed of the following raw materials in parts by weight: 120 parts of polydimethylsiloxane, 6 parts of functional additives, 10 parts of polyvinylidene fluoride, 4 parts of synergistic additives, 6 parts of antioxidants and 50 parts of solvents.
[0045] In this embodiment, it should be noted that polydimethylsiloxane was purchased from Jinan Yingyu Chemical Co., Ltd., and polyvinylidene fluoride was purchased from Suzhou Huida Plastics Import and Export Co., Ltd.
[0046] The preparation process of the functional additive is as follows: The zirconia fiber was placed in an appropriate amount of γ-aminopropyltriethoxysilane at a solid-liquid ratio of 0.22 g / mL, treated at 220 r / min for 100 min, filtered, washed with deionized water for 4 times, and dried at 100°C to constant weight to obtain modified zirconia fiber; The multi-walled carbon nanotubes were placed in an appropriate amount of deionized water and ultrasonically treated for 60 min at a solid-liquid ratio of 0.32 g / mL to obtain a suspension; An appropriate amount of modified zirconia fiber was placed in a suspension at a mass ratio of 0.4:1, treated at 34°C and 110 r / min for 24 hours, filtered, and dried in an oven at 60°C for 24 hours. The dried product was placed in a constant temperature device, and ozone was introduced into it. It was treated at 75°C for 34 minutes to obtain a functional additive.
[0047] Furthermore, the ozone introduction rate was 22 g / h, the concentration was 1000 ppm, and the introduction time was 34 min.
[0048] In this embodiment, it should be noted that the multi-walled carbon nanotubes were purchased from Shanghai Xiangtian Nanomaterials Co., Ltd., and the zirconium oxide fibers were purchased from Angxing New Carbon Materials Changzhou Co., Ltd.
[0049] The preparation process of the synergistic agent is as follows: The potassium tetratitanate whiskers were ultrasonically dispersed in an appropriate amount of deionized water at a solid-liquid ratio of 0.15 g / mL for 30 minutes to obtain a first solution; The tin chloride pentahydrate was placed in an appropriate amount of deionized water at a solid-liquid ratio of 0.22 g / mL, and treated at 140 r / min for 30 min. An oxalic acid solution with a mass percentage of 0.23% of the tin chloride pentahydrate was added thereto, and the stirring treatment was continued for 20 min to obtain a second solution; The first solution was added to the second solution at a mass ratio of 0.23:1, and the pH was adjusted to 2.6 with sodium hydroxide, and the mixture was treated at 56°C and 80 r / min for 240 min, and then dried at 80°C to constant weight; The obtained dried product was placed in a vacuum calcination device and treated at 400° C. for 70 min to obtain an intermediate product; Basalt fiber was placed in an appropriate amount of γ-aminopropyltriethoxysilane at a solid-liquid ratio of 0.23 g / mL, treated at 100 r / min for 70 min, filtered, washed with deionized water for 4 times, and dried at 100 °C to constant weight to obtain modified basalt fiber; The modified basalt fiber was placed in an appropriate amount of N,N-dimethylformamide at a solid-liquid ratio of 0.28 g / mL and ultrasonically treated for 30 minutes. The intermediate product was then added thereto and treated in a 70°C water bath for 24 hours. After filtration, it was washed four times with deionized water and then dried at 80°C to constant weight to obtain a synergistic additive.
[0050] Furthermore, the oxalic acid solution is prepared by mixing oxalic acid and water in a mass ratio of 0.66:1.
[0051] The addition amount of the intermediate product is 22% of the modified basalt fiber.
[0052] In this embodiment, it should be noted that the basalt fiber was purchased from Taian Zhirong Engineering Materials Co., Ltd.
[0053] Wherein, ethanol is selected as the solvent.
[0054] The antioxidant used is antioxidant CA.
[0055] In addition, this embodiment also provides a method for preparing the above-mentioned high-strength environment-resistant antistatic polarizer protective film, comprising the following steps: Step 1, accurately weighing polydimethylsiloxane, functional additives, parts of polyvinylidene fluoride, synergistic additives, antioxidants and solvents, and putting polydimethylsiloxane, functional additives, parts of polyvinylidene fluoride, synergistic additives, antioxidants and solvents into a mixing device for mixing and stirring to obtain a mixture; Step 2: coating the mixture on a molding device, and baking the molding device coated with the mixture to obtain a high-strength, environment-resistant, antistatic polarizer protective film.
[0056] The baking temperature is 240°C and the baking time is 200 min.
[0057] Comparative Example 1: The difference from Example 1 is that this example does not contain a functional additive.
[0058] Comparative Example 2: The difference from Example 1 is that this example does not contain a synergistic aid.
[0059] Performance test: The samples of high-strength environmentally resistant antistatic polarizer protective films provided in Examples 1 to 3 and Comparative Examples 1 to 2 are marked as Examples 1 to 3 and Comparative Examples 1 to 2, respectively; and the relevant properties of the high-strength environmentally resistant antistatic polarizer protective films provided in Examples 1 to 3 and Comparative Examples 1 to 2 are tested as follows: 1. Tensile strength and elongation at break test: The test method is ISO527-1:2012&ISO527-3:1995 / Cor.2:2001, the sample width is 25mm, the sample thickness is 0.196mm, the test speed is 500mm / min, the chuck distance is 50mm, the test environment temperature is 23±2℃, and the test environment humidity is 50±5%RH.
[0060] 2. Environmental resistance test: Cut the protective film into 300*25mm size, stick the protective film on the surface of the polarizer and put it into the UV aging test box (model: Q-LAB). After aging for 6 hours under a UV fluorescent lamp with a rated power of 40W, observe whether there are wrinkles on the surface of the protective film. If not, it is judged to be OK.
[0061] 3. Anti-static performance test: Test in accordance with the testing standard of GB / T33398.
[0062] The obtained test data are recorded in Tables 1 to 3 below.
[0063]
[0064]
[0065]
[0066] By comparing and analyzing the relevant data in Tables 1 and 2, it can be seen that the high-strength environmentally resistant antistatic polarizer protective film prepared by the present invention not only has good mechanical properties, but also has excellent environmental resistance and antistatic properties, effectively ensuring its quality. This shows that the high-strength environmentally resistant antistatic polarizer protective film and the preparation method thereof provided by the present invention have a broader market prospect and are more suitable for promotion.
[0067] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0068] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A high-strength environment-resistant antistatic polarizer protective film, characterized in that: The invention is composed of the following raw materials in parts by weight: 10 to 20 parts of polydimethylsiloxane, 3 to 6 parts of functional additives, 5 to 10 parts of polyvinylidene fluoride, 2 to 4 parts of synergistic additives, 3 to 6 parts of antioxidants and 20 to 50 parts of solvents; The preparation process of the functional additive is as follows: The zirconia fiber is placed in an appropriate amount of γ-aminopropyltriethoxysilane at a solid-liquid ratio of 0.02 to 0.22 g / mL, treated at 120 to 220 r / min for 80 to 100 min, filtered, washed with deionized water for 2 to 4 times, and dried at 70 to 100° C. to constant weight to obtain modified zirconia fiber; The multi-walled carbon nanotubes are placed in an appropriate amount of deionized water and ultrasonically treated for 40 to 60 minutes at a solid-liquid ratio of 0.02 to 0.32 g / mL to obtain a suspension; An appropriate amount of modified zirconia fiber is placed in a suspension at a mass ratio of 0.1 to 0.4:1, treated at 30 to 34°C and 80 to 110 r / min for 22 to 24 hours, filtered, and dried in an oven at 60°C for 24 hours. The obtained dry product is placed in a constant temperature device, and ozone is introduced into it, and treated at 75°C for 30 to 34 minutes to obtain a functional additive; The preparation process of the synergistic aid is as follows: The potassium tetratitanate whiskers are placed in an appropriate amount of deionized water and ultrasonically dispersed for 20 to 30 minutes at a solid-liquid ratio of 0.05 to 0.15 g / mL to obtain a first solution; Place tin chloride pentahydrate in an appropriate amount of deionized water at a solid-liquid ratio of 0.12-0.22 g / mL, treat at 120-140 r / min for 20-30 min, add 0.13-0.23% oxalic acid solution by mass of tin chloride pentahydrate, continue stirring for 10-20 min, and obtain a second solution; The first solution is added to the second solution at a mass ratio of 0.03 to 0.23:1, and the pH is adjusted to 2.2 to 2.6 with sodium hydroxide, and the mixture is treated at 50 to 56° C. and 60 to 80 r / min for 200 to 240 min, and then dried at 70 to 80° C. to constant weight; The obtained dried product is placed in a vacuum calcination device and treated at 380-400° C. for 60-70 minutes to obtain an intermediate product; The basalt fiber is placed in an appropriate amount of γ-aminopropyltriethoxysilane at a solid-liquid ratio of 0.03-0.23 g / mL, treated at 80-100 r / min for 60-70 min, filtered, washed with deionized water for 2-4 times, and dried at 70-100° C. to constant weight to obtain modified basalt fiber; The modified basalt fiber is placed in an appropriate amount of N,N-dimethylformamide at a solid-liquid ratio of 0.11 to 0.28 g / mL and ultrasonically treated for 20 to 30 minutes. The intermediate product is then added thereto and treated in a 70°C water bath for 22 to 24 hours. After filtration, the fiber is washed with deionized water for 2 to 4 times and then dried at 70 to 80°C to constant weight to obtain a synergistic additive.
2. The high-strength environment-resistant antistatic polarizer protective film according to claim 1, characterized in that: The ozone introduction rate is 20-22 g / h, the concentration is 1000 ppm, and the introduction time is 30-34 min.
3. The high-strength environment-resistant antistatic polarizer protective film according to claim 1, characterized in that: The oxalic acid solution is prepared by mixing oxalic acid and water in a mass ratio of 0.56 to 0.66:
1.
4. The high-strength environment-resistant antistatic polarizer protective film according to claim 1, characterized in that: The addition amount of the intermediate product is 11-22% of the modified basalt fiber.
5. The high-strength environment-resistant antistatic polarizer protective film according to claim 1, characterized in that: The solvent is selected from any one of ethanol and acetone.
6. The high-strength environment-resistant antistatic polarizer protective film according to claim 1, characterized in that: The antioxidant is selected from any one of antioxidant 1010, antioxidant 1076, and antioxidant CA.
7. A method for preparing a high-strength environment-resistant antistatic polarizer protective film according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1, accurately weighing polydimethylsiloxane, functional additives, parts of polyvinylidene fluoride, synergistic additives, antioxidants and solvents, and putting polydimethylsiloxane, functional additives, parts of polyvinylidene fluoride, synergistic additives, antioxidants and solvents into a mixing device for mixing and stirring to obtain a mixture; Step 2: coating the mixture on a molding device, and baking the molding device coated with the mixture to obtain a high-strength, environment-resistant, antistatic polarizer protective film.
8. The method for preparing a high-strength environment-resistant antistatic polarizer protective film according to claim 7, characterized in that: The baking temperature is 220-240° C. and the baking time is 180-200 min.
Citation Information
Patent Citations
A polarizer protective film
CN106675464B
Composite polarizer protective film and preparation method thereof, polarizer and display device
CN111454473A
Antistatic antibacterial film material
JP2019093623A
Thermally expandable refractory
JP7074924B1
Cited By
Self-cleaning anti-fouling artificial outer wall composite insulation marble film material and preparation method thereof
CN119978672A